PENGARUH KONSUMSI GUDEINA BAR TERHADAP KADAR GLUKOSA DARAH PENDERITA DIABETES MELITUS TIPE 2 - Ajeng Silpilawati; Yunita Nazarena; Terati .; Eliza .; Manuntun Rotua; Imelda Telisa (Universitas Muhammadiyah Semarang, 2025)
Diabetes Mellitus is a pathological condition characterized by chronically elevation blood glucose levels due to insulin deficiency or resistence. Non-pharmacological therapy includes consumption of low-calorie foods, low glycemic index and high fiber foods. Gudeina bar is a functional snack alternative made from purple sweet potato, soybean and dragon fruit was rich in complex carbohydrates and high fiber, provided in amounts of 39 – 59 grams/day for three days. Purpose to determine the effect of Gudeina bar consumption on blood glucose levels of patients with type 2 diabetes mellitus at the Padang Selasa Public Health Center. Methods, this quasi experimental study used one group pre-test and post-test design. The research was conducted from April 2024 to January 2025, the research involved 30 purposively selected outpatients with type 2 diabetes mellitus who met the inclusion criteria. Result The average blood glucose levels before the intervention was 291.80 mg/dL, which decreased to 257.37 mg/dL after the intervention, showing a reduction of 41.43 mg/dL. Statistical analysis using a paired t-test revealed difference. Conclusion, there was an effect of Gudeina bar consumption on blood glucose levels of patients with type 2 diabetes mellitus at the Padang Selasa Public Health Center in Palembang.